Do routine activities help predict young adults’ online harassment: a multi-nation study - Näsi, Matti (Criminology & criminal justice, 2017)
This study examined the feasibility of routine activity theory in predicting online harassment victimization of people aged 15 to 30 years in the USA, Finland, Germany, and the UK. Logistic regression models controlled for socio-demographic factors, exposure to offender, target suitability, and absence of guardianship. According to the results, between 15 percent and 20 percent of respondents reported having been victims of online harassment. Of routine activity theory variables tested, only exposure to offenders was statistically significant in each of the four countries. Females were more likely to be victims than males in Finland, but not in other countries. Those with an immigrant background had a higher likelihood of being victims in Germany, but not in the other countries, whereas the protective role of guardianship was supported in the USA and Germany. Our findings indicate that while routine activity theory is a useful tool for predicting online victimization, its feasibility varied across countries.